A descriptive study of the morbidity pattern of older persons presenting at a geriatric centre in southwestern Nigeria. (2017)
Context: Rapid population ageing is a demographic reality in most countries of the world. Old age is associated with changes which may culminate in health problems, necessitating provision of appropriate preventive, curative, and rehabilitative services. However, reports from many low- and middle-income countries have shown lack of preparedness to cater for the healthcare needs of older persons. Aim: This study described the morbidity profile and its determinants among persons aged 60 years and above who presented at an established geriatric centre in southwestern Nigeria. Materials and Methods: Data were obtained from electronic health records of 4886 patients aged ≥60 years who visited the facility between 1st January 2013 and 31st December 2014. Data were analyzed using Stata version 13 (Texas, USA). Frequency distributions were used for descriptive analysis, and chi-square test was used to test associations. Results: More than a half, 2919 (59.7%), of the respondents were females and almost three quarters 3501 (71.7%) were aged between 60 and 74 years. Mean number of morbidities was 1.81 ± 0.9, and less than half, 1097 (42.0%), presented with only one morbidity, most commonly, hypertension. There were significant age-related differences for musculoskeletal (P = 0.001), endocrine (P = 0.01), and psychological problems (P = 0.01). In addition, gender differences were observed as a significantly higher proportion of females presented with general symptoms (P = 0.02) and musculoskeletal problems (P = 0.0001) than men. Conclusion: The most common presenting morbidities at this geriatric health centre were mostly no communicable diseases. Information obtained will be useful in the design of similar facilities in other parts of the country and region at large.